(untitled) (Iranian Journal of Kidney Diseases, 2021)
Monoclonal immunoglobulin deposition disease (MIDD) is a rare disease characterized by the non-fibrous deposition of monoclonal immunoglobulin molecules along the glomerular or tubular basement membrane in kidney. We report herein the details of one case of heavy chain deposition disease (HCDD) diagnosed by renal biopsy, a relatively rare subtype of MIDD. DOI: 10.52547/ijkd.6484